Get the answers you need at Westonci.ca, where our expert community is dedicated to providing you with accurate information. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.

Solve for [tex]\( x \)[/tex]:

[tex]\[ x^2 + 6x + 8 = 0 \][/tex]


Sagot :

To solve the quadratic equation [tex]\( x^2 + 6x + 8 = 0 \)[/tex], follow these detailed steps:

1. Identify the coefficients:
The general form of a quadratic equation is [tex]\( ax^2 + bx + c = 0 \)[/tex].
Here, [tex]\(a = 1\)[/tex], [tex]\(b = 6\)[/tex], and [tex]\(c = 8\)[/tex].

2. Analyze the quadratic equation for factoring:
Factoring a quadratic equation involves writing it as a product of two binomial expressions. Look for two numbers that multiply to [tex]\(ac\)[/tex] (which is [tex]\(1 \cdot 8 = 8\)[/tex]) and add to [tex]\(b\)[/tex] (which is 6).

The numbers that multiply to 8 and add to 6 are 2 and 4.

3. Write the equation in factored form:
Rewrite the middle term, [tex]\(6x\)[/tex], as a sum of two terms using the numbers found in the previous step:
[tex]\[ x^2 + 6x + 8 = x^2 + 2x + 4x + 8 \][/tex]

4. Group and factor by grouping:
Group terms to factor by grouping:
[tex]\[ (x^2 + 2x) + (4x + 8) \][/tex]
Factor out the greatest common factor from each group:
[tex]\[ x(x + 2) + 4(x + 2) \][/tex]
Notice that [tex]\((x + 2)\)[/tex] is a common factor:
[tex]\[ (x + 2)(x + 4) \][/tex]

5. Set each factor equal to zero and solve for [tex]\(x\)[/tex]:
Set each factor equal to zero to find the solutions to the equation:
[tex]\[ x + 2 = 0 \quad \text{or} \quad x + 4 = 0 \][/tex]
Solving these equations:
[tex]\[ x = -2 \quad \text{or} \quad x = -4 \][/tex]

Therefore, the solutions to the equation [tex]\( x^2 + 6x + 8 = 0 \)[/tex] are [tex]\( x = -2 \)[/tex] and [tex]\( x = -4 \)[/tex].